TEN-YEAR TREND OF MALARIA PREVALENCE IN KALTUNGO GENERAL HOSPITAL, GOMBE STATE, NIGERIA - ABUBAKAR, BINTA; AHMAD MAGAJI, MUSA; DATHEH BELLO, PATRICK; DANJUMA JOSHUA, HABIBA; MUHAMMAD UMAR, SHAMSIYA; ELI ISHAKU, EDITH; BARNABAS TAKTAK, DANTA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Malaria is a killer disease commonly found in many tropical countries including Nigeria. Malaria attacks can cause severe sickness including high fever and body ache and can lead to death if not treated or managed properly. Malaria is commonly transmitted by an infected female Anopheles mosquito. The study sought to assess ten years (2012-2021) trend of malaria prevalence in Kaltungo Gombe State, Nigeria. Retrospective data was extracted from the diseases surveillance database of Kaltungo General Hospital, Gombe State, Nigeria. Descriptive statistics were used to analyze the data. A total of 109,123 blood films were tested for malaria in ten years, 16,563 (15.18 %)tested positive. The year 2013 had the highest number of malaria-positive cases 2321 (14.01 %) while 2014 had the least positive cases of 1060 (6.40 %) and the month of October had the highest positive cases 2030 (12.51 %) and the month of May had the least positive cases of 860 (5.19 %) and gender base females had the highest positive cases in ten-years with 8499 (51.31 %) and males with 8064 (48.69 %). The study has revealed the presence of malaria transmission throughout the years under review; hence control and preventive measures should be geared toward months that show high prevalence for effective result.